If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -6x = -51 Solving -3 + -6x = -51 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -6x = -51 + 3 Combine like terms: -3 + 3 = 0 0 + -6x = -51 + 3 -6x = -51 + 3 Combine like terms: -51 + 3 = -48 -6x = -48 Divide each side by '-6'. x = 8 Simplifying x = 8
| 6a+7b=69 | | 42/0.4 | | -10=5/6n-7-1/3n | | l+3+4xw= | | 2(p+13)+7=8(5-p)-3(-7-3p)+4 | | n/19=16 | | 1.6x-1.3x-1=8 | | X-30=125 | | (-4x+11)= | | 3(2a+b-3c)= | | (x+4)+(3x-7)= | | k/2=-20 | | (2x+10)2=(3x-55)2 | | -1+3.3h=-16 | | (8x)0(8x)= | | 50+6m= | | 9+x=-8x-18 | | X=50-46 | | (2x^3-2/7)^3 | | 3y+3+2y+6=10y-31 | | -9+3n=-63 | | g(n)=25-49(n-1) | | k/3=-16 | | ((2x^3-2/7))^3 | | -32=-17+x | | 99=9y | | -0.6u-9=-5 | | 2(3z-1)-2(4-2Z)=8 | | 13x-7=12x-12+x+5 | | -3/2y=22 | | 75-9n= | | p/14=1 |